Team sport in a COVID-19 world - a catastrophe-in-waiting, or a disguised opportunity to evolve and contribute further to population health? - Griffin, S. A.; Mendham, A. E.; Krustrup, P.; Murray, A.; Peirce, N.; Larkin, J.; Jaques, R.; Cowie, C.; Stokes, K. A.; Kemp, S. P. T. (British Journal of Sports Medicine, 2020)
Team sport has been widely hailed as a potential morale-booster for the wider society in the current COVID-19 climate (in both a spectating and participating capacity). However, team sport for most around the world is presently on hold. There is a tangible decrease in physical activity levels across the population, and experts predict a profound impact on both physical and mental health as a result of the COVID-19 crisis. Team sports increase leisure-time physical activity, and also have psychosocial benefits. Some patients recovering from COVID-19 require significant rehabilitation, and sport is a great way to help the process.